Integrating clinical trial landscapes and bibliometric analysis: unveiling the impact of PD-1/PD-L1 inhibitors on renal cell carcinoma research and therapeutic trajectories summary - Huang, Yuanbin; Ma, Xinmiao; Zhu, Hengxing; Shen, Chen; Hu, Ke; Yu, Yang; Yang, Aoyu; Liu, Zhuo; Liu, Chuanyang; Shi, Wenrui; Wang, Wei; Xia, Xueyan; et al. (Frontiers in Immunology, 2025)
BackgroundRenal cell carcinoma (RCC) is a prevalent tumor of the urinary system. Beyond surgical treatment, targeted therapies and immunotherapies are the primary therapeutic options for RCC. Although immunotherapy has been extensively studied, research on the association between the immune checkpoint PD-1/PD-L1 and RCC remains relatively novel. Thus, we aim to assess the global scientific outcomes of studies focusing on PD-1/PD-L1 in RCC from 2005 to 2024 and to identify emerging research trends.MethodsData were collected from the Web of Science Core Collection using a predefined search strategy. A total of 1,597 articles were ultimately included. In addition, 258 clinical trials registered on ClinicalTrials.gov from 2011 to 2024 were reviewed to evaluate the translational progress and global research activity. The articles were visualized and analyzed using GraphPad Prism and the bibliometric tools CiteSpace and VOSviewer.ResultsThe number of publications in this field has shown a consistent upward trend, with a marked increase starting in 2013 and peaking in 2021. At the national level, the United States ranks first in both the number of publications (n = 625) and total citations (n = 68,687). At the institutional level, Harvard University is the most productive and most cited institution among all contributors. The Journal for Immunotherapy of Cancer published the highest number of articles (n = 66), whereas the New England Journal of Medicine was the most frequently co-cited journal (n = 1,300), indicating its authoritative influence. Notable individual contributors, including Choueiri TK and Motzer RJ, have played pivotal roles in advancing research, particularly in first-line combination therapies for RCC. Frequently occurring keywords such as “immunotherapy,” “nivolumab,” “expression,” and “immune checkpoint” reflect current research hotspots and suggest future directions in this domain. Clinical trial analysis revealed that most studies were early-phase, sponsor-driven, and regionally heterogeneous in design and outcomes, highlighting both the promise and the ongoing challenges of clinical translation.ConclusionThis study provides domestic and international researchers with a comprehensive overview of the current research landscape surrounding PD-1/PD-L1-based immunotherapy in RCC. Moreover, it identifies emerging research trends and translational progress, thereby offering valuable guidance for subsequent scientific investigations and clinical application.